a Studi Komparatif Hermeneutika Kontekstual Dan Qira’ah Mubadalah Tentang “Dua Banding Satu” Harta Warisan (Qs Al-Nisa - yusran (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2024)
This paper discusses the expression two to one listed in QS al-Nisa>' 11. This paper seeks to record the views of the two figures, namely Abdullah Saeed and Faqihuddin Abdul Kodir, which according to the author, there is a re-reading of religious texts, especially in QS al-Nisa>' 11. This paper uses qualitative research with the type of library research (literature) by referring to primary sources, namely the book Interpreting the Qur'an: Towards a Contemporary Approach and Faqihuddin Abdul Qadir's book entitled Qirā'ah mubādalah. The results of the study show that in understanding inheritance, both of them view that "two to one" must be interpreted contextually, which according to Saeed needs to be adjusted to the needs of today's society and adhere to the principles of justice. Meanwhile, Faqihuddin thinks that the verse must adhere to the principle of equality between men and women. Both views boil down to one idea, namely that the Quran is a holy book that protects the equality of women and men as humans who complement each other.